1416. Piperacillin/Tazobactam Therapeutic Drug Monitoring: True Interpatient Variability or Compound Instability?. (26th November 2018) - Crass, Ryan L; Kumar, Praveen; Patel, Twisha S; Pai, Manjunath P
Abstract: Background: β-Lactam exposure is frequently documented to be inadequate in critically ill patients implying that therapeutic drug monitoring (TDM) may be necessary to optimize efficacy. Practical barriers to implementation of TDM for β-lactam/β-lactamase inhibitor combinations include potential chemical instability as well as the need to assay both drug components. Methods: First, ex-vivo stability studies of piperacillin/tazobactam (PIP/TZB) were performed at 1, 10, and 100 mg/L concentrations in human plasma. Spiked plasma samples were stored at room temperature for 4 hours and then at 4°C for 72 hours to mimic the conditions of routine handling. Second, a pilot study using discarded clinical laboratory samples was conducted to ascertain the feasibility of such a method for PIP/TZB TDM. Consecutive patients initiated on PIP/TZB within 24 hours of admission to the medical intensive care unit were screened for enrollment. Patients receiving less than 48 hours of therapy and those requiring renal replacement therapy were excluded. Laboratory samples were collected following their intended use and assayed for PIP and TZB using LC-MS/MS. Clinical patient data were obtained retrospectively. Results: In the ex vivo studies, both PIP and TZB were stable at 100 mg/L for up to 48 hours at 4°C; however, at lower drug concentrations there was unacceptable (>15%) loss after 24 hours. Thirty-two subjects contributed a total of 136 clinical samples for secondary analysis. Patients were a mean (SD) of 64 (15) years old with estimated creatinine clearance of 97 (61) mL/minute. The assay was linear over a range of 1–100 μg/mL and 0.5–50 μg/mL for PIP and TZB, respectively. The median (fifth, 95th percentile) PIP and TZB concentrations were 26.30 (1.78, 112.00) and 7.55 (0.95, 23.00) mg/L, respectively. A strong linear relationship ( R 2 0.84) was found between TZB and PIP concentrations (figure). Conclusion: PIP and TZB concentrations are strongly correlated permitting evaluation of PIP as the key analyte. Plasma samples for PIP/TZB should be frozen soon after collection for batch assay Methods. "Real-world" studies documenting high interpatient variability in PIP/TZB pharmacokinetics in the critically ill should account for pre-analytical variation due to sample degradation with clear sample handling protocols. Disclosures: All authors: No reported disclosures.